2008
DOI: 10.1152/physiolgenomics.00185.2007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influence on immune phenotype revealed strain-specific variations in peripheral blood lineages

Abstract: Inbred mouse strains are routinely used as genetically defined animal models for studying a wide assortment of biological and pathological processes, including immune system function. However, no studies have presented large-scale data on the immune cell populations among the inbred strains in physiological conditions. Here we present a systematic, quantitative analysis of peripheral blood cell phenotypes of 30 mouse strains assessed by flow cytometry. This cohort of mice represents a wide range of genetic ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…In SJL/J mice, incidence of immunizationinduced EAE is significantly higher in female mice. This observation is paralleled by elevated levels of circulating CD4 + T cells in female, as compared with male SJL/J mice (40). Interestingly, castration of SJL/J male mice leads to an increase in EAE severity.…”
Section: Discussionmentioning
confidence: 87%
“…In SJL/J mice, incidence of immunizationinduced EAE is significantly higher in female mice. This observation is paralleled by elevated levels of circulating CD4 + T cells in female, as compared with male SJL/J mice (40). Interestingly, castration of SJL/J male mice leads to an increase in EAE severity.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, the above studies that found increased corticosterone concentrations in EE-caged mice used C57BL/6 and C3H/eB strains. It will be interesting to use other strains of laboratory mice in our standardized approach to EE, both to determine whether it is an effective tool for corticosterone reduction across genetic strains and to address the high degree of variability that exists in immune phenotype across strains (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to biotechnology, there are also numerous applications in medicine, for example, blood analysis [286,287], bone marrow diagnostics [288,289], immune phenotyping [290,291], and AIDS research [292]. Fluorescence In Situ Hybridization (FISH) Fluorescence in situ hybridization (FISH) is a special form of in situ hybridization, a molecular method to detect nucleic acids (DNA or RNA) in tissues, cells, or metaphase chromosomes by fluorescence.…”
Section: Fluorescence Methodsmentioning
confidence: 99%